Situating Globalization Views from Egypt - Nelson, Cynthia; Rouse, Shahnaz (Globaler lokaler Islam, 2000)
The range of perspectives and original materials dealt with by each author highlights the renewed urgency of the struggle for cultural autonomy and voice within the context of globalization. In other words, each paper explores how the various processes at both the local and global level intersect to create new discourses and debates round the »indigenization of knowledge.« If a new wind of cultural decolonization is blowing through the Arab Middle East, which is having profound impact on the lives of men and women, then we should expect a new scholarship to emerge in order to grasp and understand it. This book is a contribution in that direction.